PENGELOLAAN SUMBERDAYA HUTAN OLEH PEMERINTAH VS KOMUNITAS LOKAL : UPAYA MENCARI TITIK TEMU - Titania Aulia; Heru Purwandari (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2012)
Many efforts in saving the forest resources have been done by the government to avoid a forest resources degradation. In 2003, government enacted the Halimun Salak National Park (TNGHS) for reducing forest resources depletion. By this policy, communities within the region can not occupy the area within the region of TNGHS. The differences of perceptions among government and community led to build different model. Government forest resource management program produces Model Kampung Konservasi (MKK), while the public perception in Kampung Nyungcung had been fasilitated by the NGOs to make Kampung Dengan Tujuan Konservasi (KDTK). The differences in perception among stakeholders (government, local communities, and NGOs) have led to conflict which is needed the collaborative management for taking a conflict resolution. Avoiding the conflict among stakeholders is significant requirement by searching a compromise. Key Words: forest management, perception, collaborative management model